2021
DOI: 10.1016/j.heliyon.2021.e07224
|View full text |Cite
|
Sign up to set email alerts
|

Effects of two pre-treatments, blanching and soaking, as processing modulation on non-enzymatic browning developments in three yam cultivars from Ghana

Abstract: Soaking effectively in decreased non-enzymatic browning in both fried and roasted products of yam varieties. Blanching affected non-enzymatic browning in the processed yam tissues differently for the different varieties. pH, titratable acidity and soluble solids are important in non-enzymatic browning of soaked yam tissues. Pre-treated yams have high reducing power as antioxidant activity. Reducing power of processed yam is dependent on the variety and the processing method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…The S sample exhibited the lowest pH values before and after storage, at 3.28 and 3.29, respectively. Combining the analysis of BI, the decrease in pH led to a reduction in the extent of NEB, consistent with the ndings ofQuayson et al (2021). However,Dorris et al (2018) suggested that low pH values can increase the initial BI of CA.…”
supporting
confidence: 79%
“…The S sample exhibited the lowest pH values before and after storage, at 3.28 and 3.29, respectively. Combining the analysis of BI, the decrease in pH led to a reduction in the extent of NEB, consistent with the ndings ofQuayson et al (2021). However,Dorris et al (2018) suggested that low pH values can increase the initial BI of CA.…”
supporting
confidence: 79%
“…The WI of cassava flour ranged from 80.48 to 84.05 in samples with pretreatment A, between 77.62 and 81.27 in samples with pretreatment B, and between 88.56 and 92.07 in samples with pretreatment C. The highest WI values were found in samples pretreated with C that dried at 60 • C for 3.96 h. This could imply that blanching cassava tubers for 5 min at 80 ± 2 • C in hot water was sufficient to drive an increasing non-enzymatic browning reaction. Quayson et al [43] reported that non-enzymatic browning intensities of yam decreased as soaking time increased. They also discovered that as blanching time increased, non-enzymatic browning levels increased.…”
Section: Effect Of Factors On Wimentioning
confidence: 99%
“…This is a process that strongly influences the aesthetic, physicochemical, and nutritional properties of the final product after processing. Soaking removes water-soluble components such as sugars and some organic acids by leaching [18,19].…”
Section: Introductionmentioning
confidence: 99%